Arbitral Tribunal Power to Disqualify Unethical Counsel - Cristina Florescu (Journal of Economic Development, Environment and People, 2015)
In specific matters of conflicts of interest ethical issues in connection with the parties' legal representatives could occur in the course of arbitration proceedings. The purpose of this paper is to identify and investigate the current status of the arbitral tribunals and arbitral institutions power to sanction counsel’s misconduct in the event of conflicts of interest. Parties have a fundamental right to choose the counsel and in the same time the right to an independent and impartial tribunal, therefore the source of the arbitral tribunal power to disqualify a counsel is a hot topic. There are no express provisions granting arbitrators such power, only soft law instruments, but which have no binding effect as long as the parties do not agree on them. For these reasons, two renowned cases where international arbitral tribunals have dealt with the subject are examined. Developing “truly transnational” ethical rules and their implementation by the arbitral institutions might be a solution. Arbitral tribunals are establishing this issue on the basis of the undertaken and applied international soft law (professional guidelines) which gained credibility and popularity and also became accepted international standards in the arbitration field.